The American Academy of Health Behavior 2023 Annual Scientific Meeting: "The Science of Identities: Measurement & Methods for Translational Health Behavior Research" - American Academy of Health Behavior (New Prairie Press, 2023)
The American Academy of Health Behavior (AAHB) hosted its 23rd Annual Scientific Meeting at the Grand Hyatt in San Francisco, California on March 12-15, 2023. The meeting's theme was "The Science of Identities: Measurement & Methods for Translational Health Behavior Research". This publication describes the meeting theme and includes the refereed abstracts presented at the 2023 Annual Scientific Meeting.